Proceedings of the 4th International Symposium on Pervasive Displays 2015
DOI: 10.1145/2757710.2757730
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Deploying See-Through Augmented Reality Signage in the Wild

Abstract: Typically the key challenges with interactive digital signage are (1) interaction times are short (usually in the order of seconds), (2) interaction needs to be very easy to understand, and (3) interaction needs to provide a benefit that justifies the effort to engage. To tackle these challenges, we propose a seethrough augmented reality application for digital signage that enables passersby to observe the area behind the display, augmented with useful data. We report on the development and deployment of our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In Human Computer Interaction (HCI), a key concern with public displays relates to interactivity and engagement. Considering that interaction times are short, interaction needs to be straightforward to understand (Kukka et al, 2013) and to provide a benefit that justifies the effort to engage (Colley et al, 2015). Prior work has shown that conveying tangible benefits is crucial for user engagement (Müller et al, 2009;Alt et al, 2012).…”
Section: Related Work Design For Public Displaysmentioning
confidence: 99%
“…In Human Computer Interaction (HCI), a key concern with public displays relates to interactivity and engagement. Considering that interaction times are short, interaction needs to be straightforward to understand (Kukka et al, 2013) and to provide a benefit that justifies the effort to engage (Colley et al, 2015). Prior work has shown that conveying tangible benefits is crucial for user engagement (Müller et al, 2009;Alt et al, 2012).…”
Section: Related Work Design For Public Displaysmentioning
confidence: 99%
“…Second-phase studies are many times executed in laboratory conditions with more or less functional prototypes [26] [27]. During the third phase, these prototypes are brought outside the controlled laboratory conditions to be studied in the field in actual public settings [28]. The fourth and final phase is deploymentbased research, wherein the prototypes now become more stable longitudinal deployments.…”
Section: Public Displays In Citiesmentioning
confidence: 99%
“…As they are becoming ubiquitous and cheap to deploy, displays can be found in public spaces such as airports [4], shopping centers [9] and train stations [8]. At the same time, sensing technologies are becoming increasingly available for easy and low cost integration with public displays, supporting different ways of interaction.…”
Section: Introductionmentioning
confidence: 99%